An analysis showing the objects of expenditure and the sources of revenue of the Irish Free State during the financial years 1925-26,1928-29, 1931-32, 1932-33 - Eason, J. C. M. (Statistical and Social Inquiry Society of Ireland, 1934)
These Tables bring up-to-date the more important figures which were set out in the Paper read before the Society in November, 1930. The detailed record of Expenditure in respect of each year and each group has, however, been excluded, and only summary totals are given. The elaborate classification between normal and abnormal expenditure has not been repeated. The distinction has only been preserved in these Tables in respect of Local Loans and Compensation for Property Losses, together with certain special items which arose in 1932/33. The general purpose is to submit a comparison which will show, in compact form, the fluctuations in the character of the expenditure over a series of years. At the end will be found the allocation of all Votes to the various groups; three remain ungrouped?Army, Posts and Telegraphs, and Road Fund; the others consist of 80 items compressed into 12 classes.
Read before the Society December 1st 1933
Keywords: National expenditure; National finance; Budget; 314.15